The Effect of Inflation on Economic Growth in Tanzania for the Period from 1970 to 2020 - Sanga, Goodluck John; Kongolo, Mukole; Mnongya, Rosemary (International Research Journal of MMC, 2022)
The research examines the effect of inflation on economic growth in Tanzania. The study employs the secondary time series data from 1970 to 2020 taken from the Bank of Tanzania, and the VECM is used to find the cointegration between variables to show the short-run and long run dynamics. Graphical analysis and Augmented Dickey-Fuller tests were conducted to find the unit root in the model. All variables were stationary and integrated in the same order I(1). The results show that the error correction was significantly negative. That is, the annual rate of adjustment required to achieve long-run equilibrium was 28.31 percent. Based on the findings in the short-run, the extended money supply and interest rates had negative and insignificant effects on GDP, while the exchange rate had an inversely significant effect on GDP. Inflation targeting had a favourable insignificant effect on GDP. Long-run results show that extended money supply, exchange rates, and interest rates had positive significant effects on economic growth, whereas inflation targeting had negative significant effects on GDP. It is recommended that the government, policymakers, and financial institutions focus on managing inflation by the prudent implementation of fiscal and monetary policies, and maintaining a regulation of interest rates, the extended money supply, and real exchange rates also inflation targeting should be emphasized by improving the central bank's communication, transparency, and accountability to avoid inflation volatility and stimulate economic growth.